Emergency Department Patient Perceptions of Transvaginal Ultrasound for Complications of First‐Trimester Pregnancy. (30th January 2018) - Panebianco, Nova; Shofer, Frances; O'Conor, Katie; Wihbey, Tristan; Mulugeta, Lakeisha; Baston, Cameron M; Suzuki, Evan; Alghamdi, Adel; Dean, Anthony
Abstract : Objectives: Emergency department (ED) transvaginal ultrasound (US) is underused in clinical practice. This study assessed pregnant women's perceptions of ED transvaginal US in terms of pain, embarrassment, anxiety, and willingness to receive the procedure. Secondary variables include physicians' perceptions of patients' experiences. Methods: Women undergoing US examinations for complications of first‐trimester pregnancy were prospectively surveyed before any US and after ED and/or radiology transvaginal US. Patients' and physicians' assessments of pain, embarrassment, and anxiety were measured with visual analog scales (0–100). Results: A total of 398 women were enrolled. In the pre‐US survey, the median anxiety score was 14 (interquartile range, 3–51), and 96% of patients were willing to have an ED transvaginal US if necessary. Of those who had ED transvaginal US, 96% would agree to have another examination. Patients reported minimal pain/embarrassment, and there was no difference if performed in the ED versus radiology (median pain, 11.5 versus 13; P  = .433; median embarrassment, 7 versus 4; P  = .345). Of the 48 who had both ED and radiology transvaginal US, 85% thought the ED transvaginal US was worthwhile. Physicians accurately assessed patient's embarrassment and pain (mean differences, 3.5 and –1.9, respectively; P  > .25 for both); however, they overestimated them relative to the pelvic examination (mean difference for embarrassment, 12.8; P  < .0001; pain, 8.0; P  = .01). Conclusions: Pregnant ED patients report low levels of anxiety, pain, and embarrassment, and after ED transvaginal US, 96% would agree to have the examination again. There is no difference in pain/embarrassment between ED and radiology transvaginal US. Emergency department physicians accurately assessed patients' pain and embarrassment with ED transvaginal US but overestimated them compared to the pelvic examination.